Análise de séries temporais em dados do setor do petróleo e gás natural - ARAÚJO, Felipe Bezerra Pimentel (2022)
Time series analysis is a very important tool for the comprehension of the market and for developing action plans and strategies. By studying the behavior patterns of a variable (such as trend, seasonality, and cycle) it is possible to make predictions and, hen ceforth, make more effective business decisions. The oil and natural gas sector comprise a significant amount of relevant historical series (price, production, capacity, etc.), there fore, probabilistic or stochastic models can be produced in order to make predictions that will help in decision-making. Analyzing, identifying, and predicting behavior patterns are essential strategies to reduce financial risk and, consequently, reduce capital loss and operating costs.